Totally Occluded Culprit Coronary Artery in Patients with Non-ST-Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Fernando, H.; Duffy, S.J.; Low, A.; Dinh, D.; Adrianopoulos, N.; Sharma, A.; Peter, K.; Stub, D.; Leong, K.E.; Ajani, A.; Clark, D.; Freeman, M.; et al. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2021)
The short- and long-term implications of identifying totally occluded culprit coronary arteries (TOCCA) in patients presenting with non-ST-elevation myocardial infarction (NSTEMI) have not been well studied. This study compares clinical characteristics, short- and long-term outcomes of patients with NSTEMI identified with TOCCA to that of patients with non-TOCCA undergoing percutaneous coronary intervention (PCI). We analyzed data from patients with NSTEMI undergoing single-vessel PCI within the Melbourne Interventional Group multi-center registry between 2005 and 2017. Those with TOCCA were compared to those with non-TOCCA. The primary endpoint was 30-day major adverse cardiac events (MACE). Secondary endpoints included 12-month MACE and long-term mortality. A total of 6,829 patients with NSTEMI had single-vessel PCI of which 954 (14%) had TOCCA. Most TOCCA were non-left anterior descending (right coronary artery 39% versus circumflex 33% versus left anterior descending 26%; p <0.001). Cardiogenic shock and left ventricular dysfunction were higher in the TOCCA group, but non-TOCCA patients had more baseline comorbidities. Thirty-day MACE was higher in the TOCCA group (6.7% versus 3.8%; p <0.001). Long-term mortality with an average follow-up of 4.9 years was higher in the non-TOCCA group (12% versus 18%, p <0.01). Multivariable Cox-proportional hazards regression identified TOCCA as an independent predictor of 30-day MACE (HR = 1.93; 95%CI: 1.4-2.6), but not long-term mortality, which was predicted by baseline comorbidities. In conclusion, while patients with NSTEMI with TOCCA undergoing PCI represent a more unstable subgroup early on, long-term outcomes appear more dependent on baseline comorbidities.